The Temporal Variations in Sunspot Number, Geomagnetic aa index and Southern Oscillation Index - Iratius Radiman; Hiroshi Miyake; Chatief Kunjaya; Yoji Takeoka; Muhamad Irfan Hakim; Zadrach L. Dupe (Jurnal Matematika & Sains, 2002)
A study of three monthly solar-terrestrial indices of mean sunspot number, geomagnetic aa index, and Southern Oscillation Index during period of 1882 to 2000 was carried out to find any consistent short âterm periodicities. We found 19, 22, and 26-month periodicities persistently occur in the above data, i nstead of 11-year pattern. We suggest that they might have solar activity origin.